Surgical Planning in Penetrating Abdominal Crohn's Disease - Myrelid, Pär; Soop, Mattias; George, Bruce D. (Frontiers in Surgery, 2022)
Crohn's disease (CD) is increasing globally, and the disease location and behavior are changing toward more colonic as well as inflammatory behavior. Surgery was previously mainly performed due to ileal/ileocaecal location and stricturing behavior, why many anticipate the surgical load to decrease. There are, however, the same time data showing an increasing complexity among patients at the time of surgery with an increasing number of patients with the abdominal perforating disease, induced by the disease itself, at the time of surgery and thus a more complex surgery as well as the post-operative outcome. The other major cause of abdominal penetrating CD is secondary to surgical complications, e.g., anastomotic dehiscence or inadvertent enterotomies. To improve the care for patients with penetrating abdominal CD in general, and in the peri-operative phase in particular, the use of multidisciplinary team discussions is essential. In this study, we will try to give an overview of penetrating abdominal CD today and how this situation may be handled. Proper surgical planning will decrease the risk of surgically induced penetrating disease and improve the outcome when penetrating disease is already established. It is important to evaluate patients prior to surgery and optimize them with enteral nutrition (or parenteral if enteral nutrition is ineffective) and treat abdominal sepsis with drainage and antibiotics.